Analysis of Economic Factors Driving Foreign Exchange Reserves in ASEAN 5 - Abel Januar Putra Gautama; Idah Zuhroh; Firdha Aksari Anindyntha (Jurnal Ilmu Ekonomi JIE, 2025)
Foreign exchange reserves themselves are important assets owned by a country that are used as a significant source of profit and ensure economic stability. This study aims to determine the influence of independent variables (FDI, remittances, and trade balance) on dependent variables (Foreign Exchange Reserves) in the long and short term. The object of research was in 5 ASEAN countries (Thailand, Indonesia, Malaysia, Vietnam, Cambodia) in 24 periods from 2000 to 2023. The analysis model used in this study is the Vector Autoregressive (VAR) Vector Error Correction Model (VECM) panel analysis. The results obtained from the survey include FDI having a significant positive effect and remittances having a significant negative impact, but the trade balance has no effect on foreign exchange reserves in the long term. In the short term, FDI and remittances have no effect, while the trade balance has a significant positive impact on foreign exchange reserves.